Bridging Leadership and Performance: The Mediating Role of Corporate Social Responsibility in Ethical and Organizational Contexts - Sohaib Uz Zaman; Abdul Sami; Syed Hasnain Alam (Research Journal of Psychology, 2025)
This study investigates how ethical leadership and organizational leadership impact firm performance through the mediating role of Corporate Social Responsibility (CSR) within the context of developing economies. The motivation stems from the increasing demand for socially responsible business practices and the theoretical gap in understanding how different leadership styles jointly influence financial and non-financial outcomes via CSR. A quantitative, Structural Equation Modeling using SmartPLS 4.0 was applied to test the relationships among constructs. Measurement validity and model fit were verified through Cronbach's alpha, composite reliability, AVE, and bootstrapping techniques. Ethical leadership (β = 0.40) and organizational leadership (β = 0.46) significantly influence CSR. CSR, in turn, strongly predicts financial performance (β = 0.71) and non-financial performance (β = 0.66). The study confirms CSR as a full mediator in the leadership–performance linkage, supporting stakeholder and social learning theories. This research offers a novel integrative framework linking ethical and organizational leadership to CSR and dual performance metrics. It provides empirical validation from an emerging market and contributes to leadership, CSR, and sustainability literature. Future studies should explore longitudinal impacts and cross-industry variations.